2000
DOI: 10.1053/he.2000.7123
|View full text |Cite
|
Sign up to set email alerts
|

Liver cell apoptosis in chronic hepatitis C correlates with histological but not biochemical activity or serum HCV-RNA levels

Abstract: In hepatitis C virus (HCV) infection, mechanisms responsible for liver cell damage are still poorly understood and both necrosis and apoptosis may be operative. By using terminal deoxynucleotydil transferase-mediated d-UTPbiotin nick-end labeling (TUNEL) we have evaluated and quantified apoptosis in liver biopsy specimens from 61 patients with chronic hepatitis C. All patients had detectable apoptotic cells in the liver. Presence of increased apoptotic activity was confirmed in selected cases by electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
98
3
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 38 publications
19
98
3
1
Order By: Relevance
“…In both diseases apoptosis has been recognized as an important feature of liver injury. 37,[52][53][54][55] The present data and a recent study of steatohepatitis patients 56 indicate that the increased TRAIL sensitivity in diseased liver is mediated by the elevated expression of TRAIL receptors. Apoptosis sensitivity might be further enhanced by altered expression profiles of Bcl-2 proteins or other cytotoxic events that might render diseased liver generally more susceptible to injury, regardless of the presence of death ligands.…”
Section: Discussionsupporting
confidence: 62%
“…In both diseases apoptosis has been recognized as an important feature of liver injury. 37,[52][53][54][55] The present data and a recent study of steatohepatitis patients 56 indicate that the increased TRAIL sensitivity in diseased liver is mediated by the elevated expression of TRAIL receptors. Apoptosis sensitivity might be further enhanced by altered expression profiles of Bcl-2 proteins or other cytotoxic events that might render diseased liver generally more susceptible to injury, regardless of the presence of death ligands.…”
Section: Discussionsupporting
confidence: 62%
“…5 and 6). These results were consistent with a clinical observation, in which up to 0.54% hepatocytes in chronic hepatitis C liver biopsies were found to be TUNEL-positive (Calabrese et al, 2000). Furthermore, the cell deaths observed in these animals were not readily detectable by the routine serum ALT test, a finding reminiscent of that seen in a subset of patients who have active HCV disease, as assessed by HCV RNA levels and liver histopathology, but who also exhibit persistently normal serum ALT values (Calabrese et al, 2000;Rodrigues et al, 2000;Shiffman et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…In HCV infection, hepatocyte apoptosis is emerging as an important feature of liver injury (Bantel and SchulzeOsthoff, 2003;Calabrese et al, 2000;Patel et al, 1998;Rodrigues et al, 2000;Walsh et al, 2004). The ensuing responses of cell repair, regeneration and fibrosis may be triggered by this process (Canbay et al, 2004;Takehara et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, surrogate markers such as the serum levels of aminotransferases did not significantly correlate with either the histological degree of liver injury or with the immunohistological detection of caspase activation. 26,37,43 As demonstrated by regression analysis, and unlike caspase activation measured in liver biopsies, serological detection of CK-18 fragments generally correlated with both ALT and AST levels. However, a strict correlation is mainly observed for higher CK-18 fragment levels (Ͼ500 U/L), whereas this could not be observed for lower CK-18 fragment levels.…”
Section: Discussionmentioning
confidence: 90%
“…37 We recently demonstrated that caspase activation in HCV-infected liver is not correlated to serum HCV RNA concentration. 25 In accordance with our previous observation, serum caspase activity did not correlate with the viral load in HCV-infected patients (data not shown).…”
Section: Resultsmentioning
confidence: 98%